Analisis Kepuasan Mahasiswa Terhadap Penggunaan Aplikasi Media Pembelajaran Online (Studi Pada Perguruan Tinggi Swasta Kota Palembang) - Dyah Ikhtiarti; Muhammad Nasir (Journal of Software Engineering Ampera, 2022)
This study aims to measure the level of student satisfaction with the use of online learning media applications, using the End User Computing Satisfaction (EUCS) method which consists of 5 variables, namely content, accuracy, format, ease of use. use) and timeliness. The population and samples used in this study were Bina Darma University, Muhammadiyah University and STISIPOL Candradimuka. The results of the calculation of the total score of respondents' answers on the level of student satisfaction with the use of online learning media applications obtained a score of 94%, which means that user responses strongly agree or are very good. The results of the F test in this study indicate that there is an influence between all variables on user satisfaction (Y) which is carried out together. The T test proves that the format and timeliness variables have no effect on user satisfaction while the content, accuracy and ease of use variables have an influence on user satisfaction variables.